2012
DOI: 10.5402/2012/621565
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Hypertension among Patients Receiving Antiretroviral Treatment Since 1998 in Senegal: Prevalence and Associated Factors

Abstract: Cardiovascular risk factors in people on antiretroviral treatment (ART) are poorly documented in resource-constrained settings. A cross-sectional study was conducted in 2009 to assess prevalence of diabetes and hypertension in a sample of 242 HIV-infected patients who had initiated ART between 1998 and 2002 in Dakar, Senegal (ANRS 1215 observational cohort). World Health Organization (WHO) criteria were applied to diagnose diabetes and hypertension. Multiple logistic regressions were used to identify factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
29
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 67 publications
12
29
8
Order By: Relevance
“…This average age is similar to that observed by DIOUF Assane et al [13]. Our study population belongs to one of the oldest PLHIV cohorts in Senegal.…”
Section: Epidemiological Aspectssupporting
confidence: 76%
See 1 more Smart Citation
“…This average age is similar to that observed by DIOUF Assane et al [13]. Our study population belongs to one of the oldest PLHIV cohorts in Senegal.…”
Section: Epidemiological Aspectssupporting
confidence: 76%
“…This serotype predominates in studies carried out in Senegal [13]. Nevertheless, hypertension was more frequent in patients with a double profile or in patients with HIV-2 LEYE AW F found a higher Framingham score for HIV-2 [6].…”
Section: Paraclinical Aspectsmentioning
confidence: 99%
“…10,11 The prevalence of diabetes in the present study was similar to reported rates in the general Ghanaian population, 12,13 but lower than rates among individuals with HIV in Nigeria (11% prevalence) and Senegal (15% prevalence), respectively. 14,15 In these studies, patients had been on HAART for a longer duration and on predominantly protease inhibitor-based regimes, which was very low in the current study (1%). Protease inhibitors increase the risk for dysmetabolic states, which contributes to the increased incidence of diabetes in the HIV population.…”
Section: Comparison With Previous Researchmentioning
confidence: 63%
“…37 A higher prevalence has been reported, however, in both a Senegalese cohort (28%) and a recent Ghanaian cohort (40%), which may be due to differences in baseline age and sex. 9,15,38 These findings underscore the fact that the burden of hypertension is likely to rise with an aging HIV population and should attract proportionate public health and clinical response to curb the projected increase in prevalence and its associated disease burden.…”
Section: Comparison With Previous Researchmentioning
confidence: 89%
“…There are number of modifiable, lifestyle factors associated with hypertension including obesity, overweight, cigarette smoking, alcohol, and low physical activity [810]. And there are some reports of an association between hypertension and HIV although this may be due to the use of antiretroviral drugs which may cause increased blood pressure [11]…”
Section: Introductionmentioning
confidence: 99%